(untitled) (Research, Society and Development, 2020)
Objective: to describe the main epidemiological indicators for Schistosomiasis mansoni (MS) in the municipality of Bacuri, Maranhão, Brazil. Methodology: For this, a documentary and quantitative research of these MS indicators was carried out in the chosen municipality. The time frame chosen for the research was from 2007 to 2016. The data used were collected from the Schistosomiasis Control Program (PCE) that is contained in the Health Information section of the Generic Public Domain Tabulator (TABNET) of the Department of Informatics of the Unified Health System (DATASUS). Results and Discussion: It was found that the year 2007 had the highest number of people with suspected Schistosoma infection (n = 8123). As for exams for suspected cases of Schistosoma mansoni infection, the years 2017 (n = 7237), 2009 (n = 4805), 2010 (n = 4789) and 2014 (n = 6443) were the ones with the highest amount. In 2007, 1166 (16.10%) positive cases were registered, followed by 2009 with 1122 (23.30%) and 2014 with 901 (13.90%). The low parasitic load (1 to 4 eggs) represented 68% (n = 3,947) of all cases, with treatment coverage for these individuals exceeding 95%. Conclusion: Based on the results obtained, it is worth noting that Schistosomiasis mansoni still has an endemic focus in municipalities far from urban centers, such as the city evaluated in this study. Thus, it is necessary to conduct the government in order to reduce these cases.